Pengaruh Kejelasan Sasaran Anggaran Dan Pengendalian Akuntansi Terhadap Akuntabilitas Kinerja Di Badan Penelitian Dan Pengembangan Provinsi Sumatera Barat - Helza Putri Nela; Elsa Meirina (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This study aims to explain the effect of clarity on budget targets and accounting controls on performance accountability in government agencies is the goal of this study. Determination of the sample using the total sampling method. The population in this study were structural officials and staff at the Research and Development Agency for West Sumatra Province and the sample used in this study was 31 respondents. The results of empirical studies show that there is an effect of clarity of budget targets on performance accountability of government agencies, there is no effect of accounting control on accountability of government agency performance, there is an influence of clarity of budget goals and joint accounting control on performance accountability of government agencies.